Faith-based organisations and exclusion in European cities / edited by Justin Beaumont and Paul Cloke. - Beaumont, Justin; Cloke, Paul J. (Policy, 2012)
This timely book explores the role played by faith-based organisations (FBOs), which are growing in importance in the provision of social services in the European context.